If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4x + -1y) = 4(4) (4x * 4 + -1y * 4) = 4(4) (16x + -4y) = 4(4) Multiply 4 * 4 16x + -4y = 16 Solving 16x + -4y = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 16x + -4y + 4y = 16 + 4y Combine like terms: -4y + 4y = 0 16x + 0 = 16 + 4y 16x = 16 + 4y Divide each side by '16'. x = 1 + 0.25y Simplifying x = 1 + 0.25y
| -5(x+2)+6=-4 | | 1/4h=-16 | | -5(-1)+9= | | 3x+2xy+1=0 | | 1/8(18+h)=7 | | -6+5p=p+6 | | m/2+12.66=16.66 | | 90x+25(90)=80x+8*90 | | 1(8x+4y)=1(-4) | | -5s+r=t | | -14+5=-3(x+4) | | B=12-9 | | -10a-5+a-4= | | r-5s=t | | v/-21+97=108 | | -2a-4=-11-3a | | -4.9t^2+28.7t+4.2=4.2 | | z-25=-36 | | n/2+8=14 | | x-.66y=.25 | | ab-4=c | | 5.50(h+75.00)=1100.00 | | 8n-(-71)=431 | | 3x+(-4)=14 | | 1-x+7x=-17 | | -3s+8=-4 | | nm=r | | x/-2=-5-(-6) | | 4-6-r=7r-6r | | -22/2 | | -3z-2=1 | | -.20-.44a=.13 |